“We need to talk about it, test it, prevent it, and that is our job”: qualitative report on the awareness of primary care physicians regarding HIV in Ukraine - Kvasnevska, Yulia; Faustova, Mariia; Voronova, Kseniia; Basarab, Yaroslav; Lopatina, Yaroslava (Frontiers in Health Services, 2024)
IntroductionApproximately 240,000 people in Ukraine are living with HIV. Recent changes in medical legislation have significantly strengthened the role of family doctors and primary care pediatricians in the prevention, early detection and follow-up of patients with HIV. Thus, the purpose of the study was to examine the experience of primary care physicians in testing and providing care to patients with HIV.MethodsQualitative semi-structured in-depth interviews with typical representatives of the target audience from different regions of Ukraine were conducted. Inductive thematic content analysis was used to analyze the data upon standardized research protocols using the Theoretical Domain System.ResultsThe results identify knowledge, skills, motivation, barriers, and opportunities in the context of HIV testing among family doctors in Ukraine. Primary health care providers consider HIV testing of patients to be an important part of their professional activities. In most cases, HIV testing is initiated upon detection of clinical indicators or when a person is identified as a key population. Preventive testing at the request of the patient is less common. Although most family doctors believe that they are sufficiently informed to conduct testing, there is a certain knowledge gap regarding communication with the patient and further treatment in case of a positive HIV result. The main obstacle to regular HIV testing is the reluctance and resistance of patients, as well as in some cases insufficient or non-existent tests in primary health care facilities. In order to improve the situation with HIV testing among the population, family doctors believe that it is necessary to organize regular trainings and courses to improve the skills of doctors on HIV, provide primary health care facilities with sufficient tests and establish high-quality information support.ConclusionsThe obtained results clearly outline the main problems that concern family doctors in Ukraine regarding work with key vulnerable groups and persons living with HIV.